Computational study of atomic mobility in hcp Mg–Al–Zn ternary alloys. (September 2016) - Wang, Jingya; Li, Na; Wang, Chuanyun; Beltran, Juan Ignacio; LLorca, Javier; Cui, Yuwen
Abstract: The experimental data in the literature for the hcp phase of the Mg–Al–Zn ternary system have been critically reviewed. Based on the concentration profiles from the literature, the diffusion coefficients have been re-extracted using the Hall method for the impurity diffusion, and the Sauer–Freise and the Whittle–Green strategies for interdiffusion coefficients in binary and ternary systems, respectively. Moreover, extra interdiffusion coefficients were obtained from the "Darken-type" couples, which present relative maxima or/and minima at the concentration profiles. This information was assessed to obtain an atomic mobility database, by means of DICTRA software in conjunction with the CALPHAD thermodynamic description that is able to reproduce the diffusion couple experiments. Comprehensive comparisons between the calculated results and experimental values show an excellent agreement not only for the diffusion coefficient data, but also for the concentration profiles and the diffusion paths.